Child psychiatric disorder and relative age within school year: cross sectional survey of large population sample. Issue 7413 (28th August 2003) - Goodman, Robert; Gledhill, Julia; Ford, Tamsin
Abstract: Objective To test the hypothesis that younger children in a school year are at greater risk of emotional and behavioural problems. Design Cross sectional survey. Setting Community sample from England, Scotland, and Wales. Participants 10 438 British 5-15 year olds. Main outcome measures Total symptom scores on psychopathology questionnaires completed by parents, teachers, and 11-15 year olds; psychiatric diagnoses based on a clinical review of detailed interview data. Results Younger children in a school year were significantly more likely to have higher symptom scores and psychiatric disorder. The adjusted regression coefficients for relative age were 0.51 (95% confidence interval 0.36 to 0.65, P < 0.0001) according to teacher report and0.35 (0.23 to 0.47, P = 0.0001) for parental report. The adjusted odds ratio for psychiatric diagnoses for decreasing relative age was 1.14 (1.03 to 1.25, P = 0.009). The effect was evident acrossdifferent measures, raters, and age bands. Cross national comparisons supported a "relative age" explanation based on the disadvantages of immaturity rather than a "season of birth" explanation based on seasonal variation in biological risk. Conclusions The younger children in a school year are at slightly greater psychiatric risk than older children. Increased awareness by teachers of the relative age of their pupils and a more flexible approach to children's progression through school might reduce the number of children with impairing psychiatric disorders in the general population.